Teatime in the Serengeti: macrodetritivores sustain recalcitrant plant litter decomposition across human-modified tropical savannahs - Anders Sundsdal; Bente J. Graae; James D. M. Speed; John Bukombe; Philipo Jacob Mtweve; Marit K. Arneberg; Vilde L. Haukenes; Ragnhild T. Grevskott; Stuart W. Smith (Plant and Soil, 2020)
Background and aims Intensification of savannah land-use is predicted to negatively influence soil biodiversity and functioning such as litter decomposition by detritivores. Loss of macrodetritivores, particularly termites, may be problematic in drier savannahs due to the capacity of macrodetritivores to sustain litter decomposition. Here we investigate how human land-use and spatiotemporal rainfall influence the contribution of macrodetritivores to plant litter decomposition. Methods We measured decomposition using globally standardized litter: labile green and recalcitrant rooibos tea litter. The contribution of macrodetritivores to litter decomposition was determined through exclusion using meshed litterbags. Litter decomposition was determined in agricultural land, pastureland and wildlife protected areas during both wet and dry seasons and in mesic and wet rainfall regions across the borders of the Serengeti National Park, Tanzania. Results Macrodetritivores consumed recalcitrant rooibos and mainly avoided labile green tea litter. On average macrodetritivores enhanced recalcitrant litter decomposition by 22%, but litter mass loss varied across land-uses, typically being higher on agricultural and pastureland compared to wildlife protected areas, and was sustained during periods of water scarcity. However, we observed instances of higher decomposition of recalcitrant litter by macrodetritivores in wildlife protected areas. In contrast, litter decomposition by microbes and microdetritivores was more constrained by seasonal and regional water availability with a minor influence of land-use. Conclusion We found that moderate human-modification of savannahs is compatible with macrodetritivore litter decomposition. As savannahs become more intensely used by humans, raising ecological awareness among agropastoralist is required to ensure continued contribution of macrodetritivores to litter decomposition.